'Squeezed' interparticle properties for plasmonic coupling and SERS characteristics of duplex DNA conjugated/linked gold nanoparticles of homo/hetero-sizes. (29th June 2016) - Skeete, Zakiya; Cheng, Han-Wen; Ngo, Quang Minh; Salazar, Christian; Sun, Winny; Luo, Jin; Zhong, Chuan-Jian
Abstract: The formation of interparticle duplex DNA conjugates with gold nanoparticles constitutes the basis for interparticle plasmonic coupling responsible for surface-enhanced Raman scattering signal amplification, but understanding of its correlation with interparticle spatial properties and particle sizes, especially in aqueous solutions, remains elusive. This report describes findings of an investigation of interparticle plasmonic coupling based on experimental measurements of localized surface plasmon resonance and surface enhanced Raman scattering characteristics for gold nanoparticles in aqueous solutions upon introduction of interparticle duplex DNA conjugates to define the interparticle spatial properties. Theoretical simulations of the interparticle optical properties and electric field enhancement based on a dimer model have also been performed to aid the understanding of the experimental results. The results have revealed a 'squeezed' interparticle spatial characteristic in which the duplex DNA-defined distance is close or shorter than A-form DNA conformation, which are discussed in terms of the interparticle interactions, providing fresh insight into the interparticle double-stranded DNA-defined interparticle spatial properties for the design of highly-sensitive nanoprobes in solutions for biomolecular detection.